Perbandingan Pengaruh Air Normal, Air Laut, dan Air Rawa Terhadap Kuat Tekan Beton - Kamil, Firmanilah; Kurnila, Nely; Suratmin, Suratmin; Faisal, M.Hanif (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
The quality of water used in concrete mixes, especially the Total Dissolved Solids (TDS) content, is often ignored despite its significant effect on the compressive strength of concrete. Normal, sea, and swamp water have different TDS characteristics, where sea water tends to have higher TDS. This study aims to analyze the relationship between the TDS value of water and the compressive strength of concrete at 7 and 28 days and identify significant differences in the compressive strength of concrete using normal, sea, and swamp water. The method used was experimental research, with samples consisting of 3 categories of water (normal, sea, and swamp) and 3 samples per category. TDS values were measured using a TDS meter, while concrete compressive strength was tested with a digital press. The research was conducted through four stages: water sampling, concrete mix preparation, molding of test specimens, and compressive strength testing. Linear regression analysis showed that the higher the TDS value, the lower the concrete compressive strength at 7 and 28 days. In addition, the ANOVA test revealed significant differences in the compressive strength of concrete at 7 days among the three types of water. These findings indicate the importance of paying attention to water quality in concrete mixes to produce optimum quality concrete. Keyword: concrete compressive strength, sea water, swamp water, TDS.